Language Variation in Tradistional Ceremony of the Batak Toba: A Sociaolinguistic Analysis - Purba, Asriaty R.; Situmorang, Rahel Theresia Rodame; Siregar, Arjuna Junifer; Tifany (Raja Zulkarnain Education Foundation, 2025)
This study aims to analyze language variation that occurs in Toba Batak traditional ceremonies through a sociolinguistic perspective. Language variation in a traditional context is understood as a socio-cultural phenomenon that reflects the identity, values, and social structure of the speaking community (Fishman, 1972). Toba Batak traditional ceremonies, such as the unjuk (showing ceremony), mangulosi (mangulosi), mangalahat horbo (showing ceremony), and traditional weddings, have distinctive and functional language structures, such as the use of umpasa (words), tutur (words), hata somba (words), and hata andung (words). These languages serve not only as a means of communication but also as a means of strengthening social relations, respect, and the transmission of cultural values (Sibarani, 2012). The research method used a descriptive qualitative approach using text analysis and literature review techniques. Data were obtained from various ritual documents, recordings of traditional ceremonies, and previous research on Toba Batak linguistics. The results indicate that language variation in Toba Batak traditional ceremonies is influenced by kinship, social status, ritual context, and specific communicative purposes (Duranti, 1997). This study finds that modern social changes influence speech styles, particularly among the younger generation, who are beginning to become familiar with Indonesian. These findings demonstrate a shift in form, but not the elimination of the cultural function of ritual language. This research contributes to the understanding of the dynamics of regional languages in cultural practices and provides a foundation for the preservation of Toba Batak linguistics in the modern era.